The Effect of Price, Information Quality, and Perceived Risk on Online Purchasing Decisions in E-Commerce - Shelvira Devi Arianda Edy Putri; Moh. Agung Surianto; Suaibatul Aslamiyah (Universitas Muhammadiyah Gresik, 2022)
The enthusiasm of the Indonesian people to shop online is currently an interesting phenomenon, the many conveniences offered when transacting online are the main attraction for buyers, but it is not uncommon for buyers to be faced with risks that will be faced when making purchases online. Moreover, there were inconsistencies in the results of previous studies regarding online purchasing decisions so it became an interesting thing to re-investigate. This study aimed to find out the effect of Price, Information Quality, and Perceived Risk on Online Purchasing Decisions in E-Commerce. The research approach used in this research was a quantitative method, according to the explanation it was causal research. The sample used was female students of the Faculty of Teacher Training and Education (FKIP), which consisted of the Study Programs of Mathematics Education, English Education, and Elementary School Teacher Education, as well as the Faculty of Islamic Religion, which consisted of the Study Programs of Islamic Religious Education, Early Childhood Islamic Education, Muhammadiyah University of Gresik Class of 2018. The data sources used were primary data and secondary data, so the results of multiple linear analyses proved that price, information quality, and perceived risk influenced online purchasing decisions in E-Commerce. so the implication of this research is that pricing, developing information quality, and well-managed perceived risk can improve online purchasing decisions in E-Commerce so it is important for economic actors to pay special attention to price, information quality, and perceived risk.